Tribological properties of silicon carbide ceramic surfaces modified by polishing, grinding and laser radiation - A. M. Abdelmagid; E. G. Orlova; D. S. Nikitin; R. S. Tsygankov; O. S. Korneva; M. A. Rudmin; D. V. Feoktistov (Discover Applied Sciences)
Abstract In this work, we experimentally studied the influence of the texture of silicone carbide (SiC) ceramics formed by traditional (grinding and polishing) and promising (laser radiation) treatment methods on tribological properties (the friction coefficient and wear rate). Raman spectroscopy was used to study the phase composition. The friction and wear tests were conducted using the ball-on disk technique under unlubricated conditions. The friction coefficient was found to be significantly affected by the texture (roughness), which must be described by at least four three-dimensional roughness parameters. The higher the surface roughness of both mechanically- and laser-treated SiC, the higher the values of wear rate and friction coefficient are. Mechanical treatment forms a texture with a negatively asymmetric and flatted distribution of asperities. The shape and density of asperities on this texture affect the friction coefficient. A texture with a negatively asymmetric and peak shaped distribution of asperities is formed by laser radiation of SiC. The skewness and the density of asperities on this texture affect the friction coefficient.